The Metabolic Response to Infection With Wolbachia Implicates the Insulin/Insulin-Like-Growth Factor and Hypoxia Signaling Pathways in Drosophila melanogaster - Currin-Ross, Denni; Husdell, Luke; Pierens, Gregory K.; Mok, Nicholas E.; O'Neill, Scott L.; Schirra, Horst Joachim; Brownlie, Jeremy C. (Frontiers in Ecology and Evolution, 2021)
The endosymbiotic bacteria, Wolbachia, are best known for their ability to manipulate insect-host reproduction systems that enhance their vertical transmission within host populations. Increasingly, Wolbachia have been shown to depend on their hosts' metabolism for survival and in turn provision metabolites to their host. Wolbachia depends completely on the host for iron and as such iron has been speculated to be a fundamental aspect of Wolbachia-host interplay. However, the mechanisms by which dietary iron levels, Wolbachia, and its host interact remain to be elucidated. To understand the metabolic dependence of Wolbachia on its host, the possibility of metabolic provisioning and extraction, and the interplay with available dietary iron, we have used NMR-based metabolomics and compared metabolite profiles of Wolbachia-infected and uninfected Drosophila melanogaster flies raised on varying levels of dietary iron. We observed marked metabolite differences in the affected metabolite pathways between Wolbachia-infected and uninfected Drosophila, which were dependent on the dietary iron levels. Excess iron led to lipid accumulation, whereas iron deficiency led to changes in carbohydrate levels. This represents a major metabolic shift triggered by alterations in iron levels. Lipids, some amino acids, carboxylic acids, and nucleosides were the major metabolites altered by infection. The metabolic response to infection showed a reprogramming of the mitochondrial metabolism in the host. Based on these observations, we developed a physiological model which postulates that the host's insulin/insulin-like-growth factor pathway is depressed and the hypoxia signalling pathway is activated upon Wolbachia infection. This reprogramming leads to predominantly non-oxidative metabolism in the host, whereas Wolbachia maintains oxidative metabolism. Our data also support earlier predictions of the extraction of alanine from the host while provisioning riboflavin and ATP to the host.